The Usefulness of the Kidney-to-Aorta Ratio in Dogs with Chronic Kidney Disease † - Dario Costanza; Erica Castiello; Pierpaolo Coluccia; Camilla Sangiuliano; Maria Pia Pasolini; Micheletino Matarazzo; Giacomo Gnudi; Adelaide Greco; Leonardo Meomartino (Veterinary Sciences)
The kidney length (KL) to aortic diameter (AoD) ratio (KL/AoD) has been proposed as an ultrasonographic objective method to assess renal dimensions. However, its wide range of normal values limits sensitivity. Of note, its clinical utility in detecting renal disease has not been investigated. The main aim of this study was to assess the sensitivity and specificity of KL/AoD in dogs with chronic kidney disease. Of the 227 dogs in the final sample, 185 were healthy and 42 were diseased. The obtained cut-off values for healthy dogs were similar to those previously reported. No differences were found between the KL of healthy and diseased dogs; however, using the KL/AoD ratio, diseased dogs showed a significantly smaller ratio (p = 0.0003), although a partial overlap between the two groups’ values was present. Considering the Youden index at KL/AoD = 6.3, the ROC curve displayed a specificity of 83.24% and a sensitivity of 41.67%, while for KL/AoD = 5.6, the specificity was 97.57% and the sensitivity was 13.10%. The results of this study provide clinical usefulness for the KL/AoD ratio method, revealing excellent specificity but poor sensitivity.